Characterization of Ceramic‐Based Construction and Demolition Waste: Use as Pozzolan in Cements. Issue 12 (24th August 2016) - Asensio, Eloy; Medina, César; Frías, Moisés; de Rojas, María Isabel Sánchez
Abstract : Depending on its composition and properties, construction and demolition waste (C&DW) may be used today as recycled aggregate to manufacture more eco‐efficient concrete, for drainage or as a sub‐base in roads and on occasion as a decorative or esthetic element in pedestrian pathways in parks and landscaped grounds. In Spain, 54% of C&DW is ceramic‐based (CB‐C&DW). Since the use of such waste as recycled aggregate is not envisaged in Spanish legislation, it is presently stockpiled in landfills, an environmentally, technically, and economically detrimental procedure. The CB‐C&DW recycled at 12 Spanish waste management plants was assessed to determine the feasibility of its use as an alternative to pozzolans such as silica fume and fly ash presently added to cement during manufacture. The proportion of ceramic‐based material contained in this recycled waste varied from plant to plant. The effect of the ceramic‐based material content on the chemical and mineralogical composition, morphology, and pozzolanic activity of CB‐C&DW was explored in a more exhaustive study of two types of waste, one with 20 and the other with 100% ceramic‐based material content. In light of its chemical and mineralogical composition, morphology and lime fixation capacity, this type of C&DW was found to be apt for use as a pozzolan, and hence as a valid alternative for manufacturing more eco‐efficient cements.